2008
DOI: 10.1016/j.seizure.2007.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and occupational risk factors for epilepsy: A nationwide epidemiological study in Sweden

Abstract: Socioeconomic status and occupation sometimes carry significantly increased risks of hospital admission for epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 22 publications
(26 reference statements)
6
26
2
4
Order By: Relevance
“…Trends in age6 and gender38 39 were largely similar to those of previous studies; however, we did not find a linear relationship between deprivation and epilepsy recording, which has been observed in studies among adults 4 40. While we found that those from the least deprived quintile of Townsend scores had the lowest incidence, it was those from the middle quintiles who had the highest incidence.…”
Section: Discussionsupporting
confidence: 87%
“…Trends in age6 and gender38 39 were largely similar to those of previous studies; however, we did not find a linear relationship between deprivation and epilepsy recording, which has been observed in studies among adults 4 40. While we found that those from the least deprived quintile of Townsend scores had the lowest incidence, it was those from the middle quintiles who had the highest incidence.…”
Section: Discussionsupporting
confidence: 87%
“…This association was not accounted for by established risk factors for epilepsy (e.g., head injury, stroke), which also have a higher incidence in low SES populations (Hesdorffer et al, 2005). In another study examining population-based data in Sweden, an increased risk of epilepsy was observed in men in who held occupations such as waiter, construction worker, or dry cleaner(Li et al, 2008) when compared to “white-collar” occupations. Those with low SES may be differently exposed to certain occupational, residential or lifestyle factors, which individuals in higher SES groups are not.…”
Section: Incidence In Studies Of Epilepsy All Unprovoked Seizuresmentioning
confidence: 99%
“…88 It is also implicated as a cause of disparities in health care, 89 including discontinuation of treatment, 90 with obvious QOL implications.…”
Section: The Role Of Sociodemographic Characteristicsmentioning
confidence: 99%